2022
DOI: 10.3389/fimmu.2022.908449
|View full text |Cite
|
Sign up to set email alerts
|

Senescent Tumor Cells in the Peritoneal Carcinomatosis Drive Immunosenescence in the Tumor Microenvironment

Abstract: More than half of all patients with colorectal cancer (CRC) develop distant metastasis and, depending on the local stage of the primary tumor, up to 48% of patients present peritoneal carcinomatosis (PC). PC is often considered as a widespread metastatic disease, which is almost resistant to current systemic therapies like chemotherapeutic and immunotherapeutic regimens. Here we could show that tumor cells of PC besides being senescent also exhibit stem cell features. To investigate these surprising findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…More evidence suggests that post-senescence stemness reprograming is also applicable in other solid tumors. It is not unique that after chemotherapy, the expression of stem-related molecules such as EpCAM, CD326, CD24, and NANOG increased in hematological tumors, liver cancer cells [ 21 ], pancreatic cancer cells, colon cancer cells, and peritoneal metastasis cells [ 46 ] ( Figure 1 ). According to studies of lung cancer model survival after radiation therapy, compared to surviving cells that received the same dose of radiation (6 times), lung cancer cells that survived after 3 doses of radiation therapy strongly expressed stem-related signals, such as CD44, CD133, and OCT4, and were associated with increased senescence-related SA-β-Gal staining [ 47 ].…”
Section: Stemness Reprograming Of Cancer Stem Cells As Well As Bypass...mentioning
confidence: 99%
“…More evidence suggests that post-senescence stemness reprograming is also applicable in other solid tumors. It is not unique that after chemotherapy, the expression of stem-related molecules such as EpCAM, CD326, CD24, and NANOG increased in hematological tumors, liver cancer cells [ 21 ], pancreatic cancer cells, colon cancer cells, and peritoneal metastasis cells [ 46 ] ( Figure 1 ). According to studies of lung cancer model survival after radiation therapy, compared to surviving cells that received the same dose of radiation (6 times), lung cancer cells that survived after 3 doses of radiation therapy strongly expressed stem-related signals, such as CD44, CD133, and OCT4, and were associated with increased senescence-related SA-β-Gal staining [ 47 ].…”
Section: Stemness Reprograming Of Cancer Stem Cells As Well As Bypass...mentioning
confidence: 99%
“…The SASP of senescent cancer cells enhanced immunosenescence (immune suppression) in the TME of peritoneal carcinomatosis (PC) to promote tumor progression [ 97 ]. Doxorubicin-induced senescence promoted the recruitment of Treg cells and myeloid-derived suppressor cells to mediate apoptotic resistance in diffuse large B-cell lymphoma (DLBCL) via pro-inflammatory cytokines, such as IL-2, IL-6, IL-8, IL-10, IL-35, TGFβ, and VEGF [ 77 ].…”
Section: Roles Of Sasp In Cancer Cell Proliferation and Therapeutic R...mentioning
confidence: 99%
“…Contrarily, senescent cancer cells have been found to support tumor spread in CRC [190]. Exploiting both human and mouse samples, Braumüller et al showed that SASP factors may lead to enhanced immuno-senescence in the TME of CRC, thus explaining its resistance to known chemo-and immunotherapeutic approaches [191]. Indeed, the authors showed that senescent cancer cells acquired a stem cell-like phenotype in both murine and human samples, possibly leading to deleterious consequences, like chemotherapy resistance.…”
Section: Senescence In Colorectal Liver Metastases (Clm)mentioning
confidence: 99%